2001
DOI: 10.1093/oxfordjournals.schbul.a006849
|View full text |Cite
|
Sign up to set email alerts
|

"Schizotaxia": Clinical Implications and New Directions for Research

Abstract: The At Issue section of the Schizophrenia Bulletin contains viewpoints and arguments on controversial issues. Articles published in this section may not meet the strict editorial and scientific standards that are applied to major articles in the Bulletin. In addition, the viewpoints expressed in the following article do not necessarily represent those of the staff or the Editorial Advisory Board of the Bulletin-The Editors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 147 publications
(163 reference statements)
0
84
0
Order By: Relevance
“…As in the domains described above, nonpsychotic relatives of schizophrenia patients demonstrate multiple deficits in cognition that are similar to those seen in schizophrenia sufferers (2,29,(48)(49)(50). Individuals with SPD, for example, show deficits in nonverbal learning, and especially in verbal learning (51), in working memory (52), and in several executive functions, including concept formation, abstraction, and mental flexibility (53).…”
Section: Neuropsychological Deficitsmentioning
confidence: 87%
See 1 more Smart Citation
“…As in the domains described above, nonpsychotic relatives of schizophrenia patients demonstrate multiple deficits in cognition that are similar to those seen in schizophrenia sufferers (2,29,(48)(49)(50). Individuals with SPD, for example, show deficits in nonverbal learning, and especially in verbal learning (51), in working memory (52), and in several executive functions, including concept formation, abstraction, and mental flexibility (53).…”
Section: Neuropsychological Deficitsmentioning
confidence: 87%
“…While some of these deficits may be present in other schizophrenia-related disorders such as SPD, they also exist independently (see [2] for further discussion of similarities and differences between SPD and schizotaxia).…”
Section: Psychosocial Functioningmentioning
confidence: 99%
“…In this broad context, we reformulated the term schizotaxia in the 1990s to integrate newer data [59]. Our conception of schizotaxia was consistent with Meehl's view of it as the underlying liability among people predisposed to schizophrenia, though aspects of his view were modified.…”
Section: Development and Validationmentioning
confidence: 73%
“…In contrast, Meehl's conception of the most direct consequence of schizotaxia -schizotypy -was considered observable, and that concept did enter the psychiatric nosology in the modified form of 'schizotypal personality disorder'. By the 1990s, however, a growing body of literature showed that a subset of non-psychotic relatives of people with schizophrenia showed a broad range of measurable abnormalities in brain structure and function, neurophysiological aspects of information processing such as eye tracking and various sensory gating paradigms, neuropsychological function, and social functioning, among others [7,8,17,59]. These findings supported the view that the notion of liability might be amenable to operational definitions, whereas it had not been previously.…”
Section: Foundations Of the Conceptmentioning
confidence: 99%
“…Consequently, Meehl [16] proposed the concept of schizotaxia, as a relatively common, clinically dormant genetic liability, expressed neurobiologically as deficits in neuronal integrity, which sometimes develop into schizophrenia or schizotypy. Faraone et al [17] and Tsuang et al [18], among others, conceptualized schizotaxia as a clinical syndrome mainly characterized by subthreshold negative symptoms and cognitive impairment, which are present in about 20–50% of relatives of schizophrenia subjects.…”
Section: Introductionmentioning
confidence: 99%